Upaya Meningkatkan Keterampilan Membaca Siswa Kelas II SD Negeri 0104 Sibuhuan Dengan Menggunakan Alat Peraga Kartu Huruf - Siregar, Lailan Aprina; Hasibuan, Efrida Sofa; Siregar, Nurhayati (Yayasan Perguruan Kampus, 2025)
The type of research used is classroom action research (PTK. The data collection technique in this research was obtained through observation and documentation. Based on the research results, it can be concluded that: (1) The reading skills of class II students at SD Negeri 0104 Sibuhuan in the pre-cycle were still low. This can be seen from the results of observations that have been made (2) The reading skills of class II students at SD Negeri 0104 Sibuhuan in cycle I have begun to improve. This can be seen from the results of observations that have been made in cycle I. The reading skills of students in the